Kepemimpinan Transformasional Kiai dalam Meningkatkan Self-Efficacy Pendidik: Studi Kasus Yayasan Darul Ulum Rebalas Pasuruan - Mukhammad Baihaqi; Miftakhul Ilmi Suwignya Putra; Moh. Makmun; Hidayati, Beti Malia Rahma (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study investigates the enduring impact of KH. Abdi Manaf’s transformational leadership on the self-efficacy of educators at Yayasan Darul Ulum Rebalas Pasuruan after his passing. Addressing the gap in existing literature, it explores how Islamic spiritual and charismatic leadership values persist within organizational culture. Using a qualitative intrinsic case study design, data were collected through interviews, participant observation, and document analysis, and analyzed thematically. Four key themes emerged: exemplary conduct, inspiration and motivation, adaptation and innovation, and the inheritance of leadership values, supported by contextual factors such as intergenerational challenges and external assistance. The findings reveal that KH. Abdi Manaf’s leadership fostered a sustainable value system that continues to guide educators’ professional identity and confidence. The study extends transformational leadership theory by integrating spiritual-cultural dimensions specific to Islamic education, offering both theoretical contributions and practical implications for leadership development and organizational sustainability